INTEGRASI ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN IPS BERBASIS METAKOGNISI - Riski Ananda; Asna Lia Clarisa; Salwa Nadhifah; Mutia Saqillah Ahyar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Technological developments in the era of the Industrial Revolution 4. 0 and Society 5. 0 has created a major change in the education sector, including through the use of Artificial Intelligence (AI) as a learning tool. This study aims to examine the application of Artificial Intelligence (AI) in the teaching of Social Sciences (IPS) which focuses on metacognition and observes its role in improving students' critical, reflective, and independent thinking skills. This study adopts a descriptive qualitative approach with literature study methods from various scientific journals, books, and related academic documents. The findings of the study show that AI is able to provide fast access to information, tailored learning, and useful feedback to increase the effectiveness of the learning process. In social studies teaching, AI helps students understand diverse social phenomena in a broader and deeper way. However, the optimal use of AI requires the support of metacognitive abilities so that students can plan, monitor, and evaluate their own learning processes. The incorporation of AI and metacognition not only improves material comprehension, but also hone critical thinking skills, creativity, problem-solving skills, digital literacy, and independence in learning. Therefore, the application of AI in social studies teaching based on metacognition can be one of the innovative approaches to support the development of competencies in the 21st century and improve the quality of education in the digital era.